Britain and the narration of travel in the nineteenth century
1 online resource (287 pages)
Keywords: "Interrogating the multiple ways in which travel was narrated and mediated, by and in response to, nineteenth-century British travelers, this interdisciplinary collection examines to what extent these accounts drew on and developed existing tropes of travel. The three sections take up personal and intimate narratives that were not necessarily designed for public consumption, tales intended for a popular audience, and accounts that were more clearly linked with discourses and institutions of power such as imperial processes of conquest and governance. Some narratives focus on the things the travelers carried such as souvenirs from the battlefields of Britain's imperial wars, while others show the complexity of Victorian dreams of the exotic. Still others offer a disapproving glimpse of Victorian mores through the eyes of indigenous peoples in contrast to the imperialist vision of British explorers. Swiss hotel registers, guest books, and guidebooks offer insights into the history of tourism, while new photographic technologies, the development of the telegraph system, and train travel transformed the visual, audial, and even the conjugal experiences. The contributors attend to issues of gender and ethnicity in essays on women travelers, South African travel narratives, and accounts of China during the Opium Wars and analyze the influence of fictional travel narratives. Taken together, these essays show how these multiple narratives circulated, cross-fertilised, and reacted to one another to produce new narratives, new objects, and new modes of travel" --